Influence of N‐Butyldithiocarbamic Acid Content on the Properties of Sb2S3 Sensitized TiO2 Nanorod Arrays and Photovoltaic Performance of the Corresponding Solar Cells. Issue 25 (1st July 2021) - Ying, Chao; Guo, Fuling; Cui, Xi; Sun, Xun; Shi, Chengwu
Abstract: In this paper, Sb2 S3 ‐sensitized TiO2 nanorod arrays are successfully prepared by the spin‐coated and then pyrolysis (denoted as spin‐pyrolysis) of Sb2 S3 precursor solution in N ‐Butyldithiocarbamic acid‐ethanol (Sb‐BDCA complex solution). The influence of precursor solution content with different mole ratios of N ‐Butyldithiocarbamic acid to Sb 3+ (6, 8 and 10, denoted as BDCA‐6, BDCA‐8 and BDCA‐10, respectively) on the crystalline phase, optical absorption and microstructure of the Sb2 S3 ‐sensitized TiO2 nanorod arrays have been investigated systematically. By adjusting the BDCA to Sb 3+ mole ratios, the superior preferred orientation of the (211) plane for Sb2 S3 was obtained. The results revealed that the Sb2 S3 ‐sensitized TiO2 nanorod arrays for BDCA‐8 showed the best conductivity and the corresponding solar cell achieved the best PCE of 5.43 % with the open‐circuit voltage ( V oc ) of 0.53 V, short‐circuit photocurrent density ( J sc ) of 17.19 mA cm −2 and fill factor (FF) of 59.21 %. After the Sb2 S3 sensitized TiO2 nanorod array was modified by lauric acid, the PCE of the corresponding solar cells increased from 5.43 % to 5.77 %. Abstract : The Sb2 S3 sensitized TiO2 nanorod arrays prepared by BDCA‐8 have the characteristics of good microstructure and superior preferred orientation of the (211) plane, and the corresponding solar cells achieved the best PCE of 5.43 %. Since the TiO2 nanorod array was not completely covered by Sb2 S3, the PCE of the solar cell surface modified by lauric acid increased from 5.43 % to 5.77 %.